Jurisprudence as a Bridge Between Normative Legal Frameworks and Social Realities - Basman; Mukhlis Achmad; Ronal Regen; Riyan Adnan Wahyudi; Priyanto; Fajar Abadi Jaya Tadjuddin S; Muh. Ramli (www.amertainstitute.com, 2026)
Normative legal frameworks, as codified systems of written rules, are fundamentally designed to ensure legal certainty and uniformity. However, their abstract and static nature often limits their capacity to respond effectively to the dynamic and complex realities of social life. This condition creates a structural gap between law in books and law in action. In this context, jurisprudence—understood as consistently followed court decisions with permanent legal force—plays a strategic role in mediating normative law and lived social realities. This study examines how jurisprudence functions as an adaptive legal instrument capable of filling legal gaps, clarifying ambiguous norms, and contextualizing the application of law in accordance with prevailing social values. Employing a normative legal research method, this study integrates statutory, conceptual, and case-based approaches to analyze judicial reasoning reflected in selected court decisions. The findings demonstrate that jurisprudence serves not merely as a supplementary source of law, but as a dynamic mechanism of legal development through judicial law-making and legal discovery (rechtsvinding). By incorporating considerations of social justice, morality, and societal needs, jurisprudence contributes to balancing legal certainty with substantive justice. Moreover, jurisprudence enhances the responsiveness and legitimacy of the legal system by translating abstract legal norms into concrete, socially relevant rulings. This study underscores the importance of jurisprudence in strengthening the interaction between normative legal structures and social realities, affirming its essential role in the pursuit of a more just, contextual, and adaptive legal order